EXPLORING THEMES OF NOVICE ENGLISH TEACHERS' TEACHING REFLECTION - Rahmi Fadilah, - (2018)
The issue about being a reflective teacher is an important part of teachers' professional development. Most studies have explored the way teacher to reflect their teaching especially in the context of pre-service and professional English teacher. However, there is a limited study about the way novice English teachers (NTs) with less than five years experiences to reflect their teaching as they have passed their beginning year to be a teacher and adapt to many challenges in their new circumstances of teaching and learning. Thus, this exploratory case study aims to explore the themes of novice English teachers' teaching reflection by looking at their understanding and practice on that. There are three participants chosen purposively in this research. The data were collected by using questionnaires, classroom observation, teachers' reflective journal, and interview. The results show that they lack of knowledge on teachers' teaching reflection because there is a difference between their understanding and practices on that. Second, years of experiences do not really influence their practice on teachers' teaching reflection. Third, they focus on reflection about themselves and students' condition as forms (habituation and introspection) and themes (evaluative and adaptive) on teachers' teaching reflection. NTs need more attention to reflect their practice outside of themselves, such as reflecting to pedagogical and professional content knowledge, the collaboration with other, and transforming their practice based on attitude, social, moral, and political issue in teaching and learning process. Keywords: Teachers' Teaching Reflection, Novice English Teacher, Professional Development, Reflection Themes. Isu tentang menjadi guru reflektif adalah bagian penting dalam perkembangan professional guru. Banyak dari penelitian telah menunjukkan bagaimana guru merefleksikan pembelajaran khususnya pada konteks guru Bahasa Inggirs muda dan guru profesional. Akan tetapi, hanya ada sedikit penelitian tentang bagaimana guru Bahasa Inggris dengan pengalaman kurang dari lima tahun (Novice English Teachers) dalam merefleksikan pembelajaran dalam situasi mereka yang telah melewati masa awal mengajar dan beradaptasi pada banyak tantangan di lingkungan baru mereka. Jadi, penelitian ini melihat pada pemahaman dan praktek mereka dalam hal tersebut. Ada tiga orang guru sebagai partisipan dalam penelitian ini yang dipilih sesuai dengan kebutuhan penelitian. Data penelitian dikumpulkan dengan menggunakan kuisioner, observasi kelas, jurnal mengajar guru, dan interview. Hasil dari penelitian menunjukkan bahwa guru-guru tersebut kurang memiliki pengetahuan tetang refleksi pembelajaran karena ada perbedaan antara pemahaman dan praktek mereka terkait hal teresebut. Kedua, jumlah tahun mereka dalam mengajar tidak mempengaruhi refleksi pembeljaran mereka. Ketiga, mereka fokus pada refleksi tentang diri mereka sendiri dan kondisi siswa sebagaimana pola (habituation and introspection) dan tema (evaluative and adaptive) dalam refleksi pembelajaran. Mereka perlu perhatian lebih untuk merefleksikan pemebelajaran diluar dari diri mereka sendiri seperti refleksi pada hal pedagogik dan profesional, berkolaborasi dengan guru lain, dan merefleksikan pembelajaran mereka pada kondisi sosial, moral, dan politik. Kata Kunci: Refleksi Pembelajaran, Novice English Teacher, Perkembangan Profesional, Tema Refleksi Pembelajaran.